Análisis, diseño e implementación de una explicación web mediante la utilización de sistemas y controles Ajax para la automatización de los procesos de la empresa municipal regional de agua potable de los cantones Arenillas y Huaquillas - Merino Gaona, Juan Carlos (2013)
The following draft thesis for Systems Engineer is based on analyzing, designing and implementing a Web application for marketing of drinking water in the Regional Municipal Water Supply Company of Arenillas and Huaquillas cantons, using systems and controls Ajax.